Study the Effect of Face Sheets Material on Strength of Sandwich Plates with Circular Hole (Journal of Engineering, 2014)
This study aims to investigate the effect of changing skins material on the strength of sandwich plates with circular hole when subjected to mechanical loads. Theoretical, numerical and experimental analyses are done for sandwich plates with hole and with two face sheet materials. Theoretical analysis is performed by using sandwich plate theory which depends on the first order shear deformation theory for plates subjected to tension and bending separately. Finite element method was used to analyse numerically all cases by ANSYS program.The sandwich plates were investigated experimentally under bending and buckling load separately. The relationship between stresses and the ratio of hole diameter to plate width (d/b) are built, by studying the effect of hole size on strength of sandwich plates. The maximum stress were developed at the hole region in sandwich plates clarified the dropped in their strength. So, the experimental maximum stress was found by means of multiplying the experimental nominal stress obtained from Stress-strain curve by the stress concentration factor.All results which obtained, theoretically, numerically and experimentally are compared to find that the hole weaken the strength of sandwich plates because of the stress concentration and that weakness is depending on the hole size and the face sheets materials.